Categorization of slope failure in southern Malaysia using total estimated hazard (TEHD) method - Raja Abd Assiss, Raja Fairol Farouk; F., R. F.; Zainorabidin, Adnan; A., A.; Zainun, 3. Noor Yasmin; Y., N. (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Slope is a measure of steepness or the degree of inclination of a feature relative to the horizontal plane. One of the phenomenon or incidents of a slope was called as slope failure or landslide. Slope failure was a major natural disaster that had affected the country in terms of injuries, deaths, property damage, destruction of services, public inconvenience and economic as well as financial losses. Slope failure cases were very serious geologic hazard disaster that happened in many countries around the world. The aim of this paper is to determine the category of slope failure in the state of Johor based on Landslide Hazard Zonation (LHZ). Data were calculated by using Total Estimated Hazard (TEHD) value method which considered six factors effecting the slope failure, including lithology; slope steepness, topography, land use class, annual rainfall and type of soil. Data on the factors were collected from Malaysia Public Works Department (JKR) inspection form, website, and secondary data resource. After that weight for each factor were identified by referring to Landslide Hazard Evaluation Factor (LHEF) rating scheme. Then determination of LHZ was done according to TEHD values which have five hazard zones; (1) very low; (2) low; (3) medium; (4) high; and (5) very high. The results of this study found that out of total fifty two cases there were three medium hazard (MH), twenty seven high hazard (HH) and twenty two very high hazard (VHH). Comparison between actual data from JKR and total 52 locations of slope failure in Johor showed that 94% accuracy, TEHD equation could calculate potential slope failure hazards in Johor very well.